Developmental pathways linked to the vulnerability of adult midbrain dopaminergic neurons to neurodegeneration - Prakash, Nilima (Frontiers in Molecular Neuroscience, 2022)
The degeneration of dopaminergic and other neurons in the aging brain is considered a process starting well beyond the infantile and juvenile period. In contrast to other dopamine-associated neuropsychiatric disorders, such as schizophrenia and drug addiction, typically diagnosed during adolescence or young adulthood and, thus, thought to be rooted in the developing brain, Parkinson’s Disease (PD) is rarely viewed as such. However, evidences have accumulated suggesting that several factors might contribute to an increased vulnerability to death of the dopaminergic neurons at an already very early (developmental) phase in life. Despite the remarkable ability of the brain to compensate such dopamine deficits, the early loss or dysfunction of these neurons might predispose an individual to suffer from PD because the critical threshold of dopamine function will be reached much earlier in life, even if the time-course and strength of naturally occurring and age-dependent dopaminergic cell death is not markedly altered in this individual. Several signaling and transcriptional pathways required for the proper embryonic development of the midbrain dopaminergic neurons, which are the most affected in PD, either continue to be active in the adult mammalian midbrain or are reactivated at the transition to adulthood and under neurotoxic conditions. The persistent activity of these pathways often has neuroprotective functions in adult midbrain dopaminergic neurons, whereas the reactivation of silenced pathways under pathological conditions can promote the survival and even regeneration of these neurons in the lesioned or aging brain. This article summarizes our current knowledge about signaling and transcription factors involved in midbrain dopaminergic neuron development, whose reduced gene dosage or signaling activity are implicated in a lower survival rate of these neurons in the postnatal or aging brain. It also discusses the evidences supporting the neuroprotection of the midbrain dopaminergic system after the external supply or ectopic expression of some of these secreted and nuclear factors in the adult and aging brain. Altogether, the timely monitoring and/or correction of these signaling and transcriptional pathways might be a promising approach to a much earlier diagnosis and/or prevention of PD.